Polymorphism patterns in Duffy-binding protein among Thai Plasmodium vivax isolates - Gosi, Panita (BioMed Central, 2008)
BACKGROUND: The Duffy-binding protein II of Plasmodium vivax (PvDBPII) has been considered as an attractive target for vaccine-mediated immunity despite a possible highly polymorphic nature. Among seven PvDBP domains, domain II has been shown to exhibit a high rate of nonsynonymous polymorphism, which has been suggested to be a potential immune (antibody binding) evasion mechanism. This study aimed to determine the extent of genetic polymorphisms and positive natural selection at domain II of the PvDBP gene among a sampling of Thai P. vivax isolates. METHODS: The PvDBPII gene was PCR amplified and the patterns of polymorphisms were characterized from 30 Thai P. vivax isolates using DNA cloning and sequencing. Phylogenetic analysis of the sequences and positive selection were done using DnaSP ver 4.0 and MEGA ver 4.0 packages. RESULTS: This study demonstrated a high rate of nonsynonymous polymorphism. Using Sal I as the reference strain, a total of 30 point-mutations were observed in the PvDBPII gene among the set of Thai P. vivax isolates, of which 25 nonsynonymous and five synonymous were found. The highest frequency of polymorphism was found in five variant amino acids (residues D384G, R390H, L424I, W437R, I503K) with the variant L424I having the highest frequency. The difference between the rates of nonsynonymous and synonymous mutations estimated by the Nei and Gojobori's method suggested that PvDBPII antigen appears to be under selective pressure. Phylogenetic analysis of PvDBPII Thai P. vivax isolates to others found internationally demonstrated six distinct allele groups. Allele groups 4 and 6 were unique to Thailand. CONCLUSION: Polymorphisms within PvDBPII indicated that Thai vivax malaria parasites are genetically diverse. Phylogenetic analysis of DNA sequences using the Neighbour-Joining method demonstrated that Thai isolates shared distinct alleles with P. vivax isolates from different geographical areas. The study reported here will be valuable for the development of PvDBPII-based malaria vaccine.